2005
DOI: 10.1152/ajpregu.00106.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational consequences of fetal programming by in utero exposure to glucocorticoids in rats

Abstract: Epidemiological studies linking low birth weight and subsequent cardiometabolic disease have given rise to the hypothesis that events in fetal life permanently program subsequent cardiovascular risk. The effects of fetal programming may not be limited to the first-generation offspring. We have explored intergenerational effects in the dexamethasone-programmed rat, a model in which fetal exposure to excess glucocorticoid results in low birth weight with subsequent adult hyperinsulinemia and hyperglycemia underp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
281
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(296 citation statements)
references
References 40 publications
13
281
0
2
Order By: Relevance
“…8 In rats paternal dexamethasone exposure in utero led to both a reduced birth weight and increased hepatic activity of the gluconeogenic enzyme, phosphoenolpyruvate carboxykinase, in future offspring. 19 Beyond studies of mutagenic agents, 20 we are not aware of any general male-line transgenerational studies in humans. This probably stems from two factors; residual scepticism 21 about the germline's susceptibility to environmentally-induced change and epigenetic inheritance (with its hint of Lamarkism), and the fact that human transgenerational studies are fraught with problems.…”
Section: Discussionmentioning
confidence: 99%
“…8 In rats paternal dexamethasone exposure in utero led to both a reduced birth weight and increased hepatic activity of the gluconeogenic enzyme, phosphoenolpyruvate carboxykinase, in future offspring. 19 Beyond studies of mutagenic agents, 20 we are not aware of any general male-line transgenerational studies in humans. This probably stems from two factors; residual scepticism 21 about the germline's susceptibility to environmentally-induced change and epigenetic inheritance (with its hint of Lamarkism), and the fact that human transgenerational studies are fraught with problems.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal exposure to dexamethasone of males mated with control females lowered birth weight in their progeny of either sex. However when dexamethasone-prenatally exposed female rats were mated with control males only the male part of the offspring was affected [62].…”
Section: Sexual Dimorphism In Consequences On Offspringmentioning
confidence: 96%
“…In addition to these malprogramming epigenetic somatic processes there are now also clear examples of transmission through the germline for both sexes, with sex-specific effects [62][63][64].…”
Section: Sex-specific Differences In Germline Transmissionmentioning
confidence: 99%
“…The early period (days 0-7) corresponds to the embryonic phase of development in the rat and in fact embryos only implant at around day 4.5. 7 The mid-gestation period (days [8][9][10][11][12][13][14] largely corresponds to the period of organogenesis, while late gestation (days [15][16][17][18][19][20][21][22] is the period of most rapid growth and differentiation of key structures. By feeding at these targeted periods, it is possible to identify when nutritional programming occurs and this can provide important indicators of potential mechanisms.…”
Section: Animalsmentioning
confidence: 99%
“…A large number of studies in rats, mice, guinea pigs and sheep have clearly shown that exposure to relatively short periods of undernutrition or endocrine disturbance in fetal life can programme raised blood pressure, glucose intolerance and insulin resistance. [7][8][9] The range of nutritional exposures capable of eliciting programmed responses in the developing offspring is broad, including micronutrient deficiency, [10][11][12] excess of saturated fat 13 and restriction of food intake (global nutrient restriction). 14,15 In the present paper, we report findings from a model of low protein feeding in rat pregnancy.…”
Section: Introductionmentioning
confidence: 99%